PERBEDAAN SIKAP KOLABORATIF SISWA BERDASARKAN GENDER DALAM PEMBELAJARAN FISIKA DENGAN MODEL COLLABORATIVE LEARNING DI KELAS X MADRASAH ALIYAH AL- IHSAN BOARDING SCHOOL KAMPAR - Riza Andriani Andriani; Zulhelmi '; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Thepurposeof this study was to describe student activity, describe and determine the significance of student attitude in collaboration based on gender after using collaborative learning model in physics at MA Al Ihsan Boarding School Kampar. This study was conducted in MA Al Ihsan Boarding School Kampar in November 2014 until May 2015 by using One Group Pretest-Posttest Design that was applied in two classes with different gender (boys class and girls class). Study subjects consisted of 10 student of boys class and 14 student of girls class. The result showed that score of boys and girls attitude in collaboration is at a high category and score of student activity is at a very high category. Before the learning, Score of girls attitude in collaboration is higher than the score of boys, but based on t-test this difference was not significant. After the learning, score of boys attitude in collaboration advance, and score of girls in collaboration decrease, but girls score are higher than boys and based on t-test this difference and alteration was not significant. Based on standar deviation obtained that girls showed the attitude in collaboration and activity more homogeneous than boys. So that, the difference of student attitude in collaboration based on gender was not significant and collaborative learning can be used to advance student activity for both boys and girls, whereas for student attitude in collaboration must be trained continuously and comprehensive, like collaborate with teachers of other subjects to implementing this learning model. Key Word : Physics, Collaborative Learning, Gender, Student Attitude in Collaboration, Student Activity